2018
DOI: 10.1021/acscentsci.8b00751
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Engineering of Bacterial Effectors for Spatial–Temporal Modulation of Cell Signaling

Abstract: The complicated and entangled cell signaling network is dynamically regulated by a wide array of enzymes such as kinases. It remains desirable but challenging to specifically modulate individual, endogenous kinases within a cell, particularly in a spatial–temporally controlled fashion. Current strategies toward regulating the intracellular functions of a kinase of interest either lack specificity or require genetic engineering that may perturb its physiological activity. Herein, we harnessed a bacterial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Subsequently, we analyzed whether deprotection with the prokaryote-compatible 3,6-dimethyl-tetrazine (26) could be used to switch on recombinant protein expression. 12,42 We found that 26 caused a minor delay on IPG (15) induced OVA expression without reducing overall expression levels ( Fig. S5 and Table S10 †).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequently, we analyzed whether deprotection with the prokaryote-compatible 3,6-dimethyl-tetrazine (26) could be used to switch on recombinant protein expression. 12,42 We found that 26 caused a minor delay on IPG (15) induced OVA expression without reducing overall expression levels ( Fig. S5 and Table S10 †).…”
Section: Resultsmentioning
confidence: 93%
“…1A). 7,8 The excellent biocompatibility and high bimolecular reaction rate of the IEDDA pyridazine elimination 9 has given rise to a multitude of in vitro and in vivo applications such as the regulation of protein activity [10][11][12] and the activation of pro-drugs, in which spatiotemporal control is achieved by antibody-drug conjugates (ADCs), [13][14][15] nanoparticles, 16 enzymatic supramolecular self-assembly 17 or hydrogel injection. 18,19 To date, nearly all applications for this reaction have relied on the protection of (primary) amines as TCO-carbamates ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the constitutively active OspF irreversibly inhibits MAPK activity, geneticallyencoded decaging strategies were recently developed to provide controlled activation of the phospholyase in different contexts, including in vivo applications. 23,24 For instance, a chemicallycaged OspF (termed OspF c ) was engineered to contain a transcyclooctene (TCO) lysine at the catalytic residue K134 which ablated activity, and an inverse electron demand Diels-Alder reaction with 3,6-dimethyl-1,2,4,5-tetrazine (Me 2 -Tz) 25,26 released the active parent Fig. 2 A chemical de-caging strategy enabling control of the phospholyase activity of the bacterial enzyme OspF that irreversibly inactivates ERK1 via dehydrobutyrine (Dhb) formation.…”
Section: Phospholyasesmentioning
confidence: 99%
“…2 A chemical de-caging strategy enabling control of the phospholyase activity of the bacterial enzyme OspF that irreversibly inactivates ERK1 via dehydrobutyrine (Dhb) formation. 23 A key step in the process is the use of the inverse electron demand Diels-Alder reaction to remove the TCO from the modified OspF to reveal the catalytic lysine that triggers phosphate elimination on p-ERK1 (OspF structure: PDB 3I0U; ERK1 structure: PDB 2ZOQ; TCO = trans-cyclooctene; Me 2 -Tz = 3,6-dimethyl-1,2,4,5-tetrazine). enzyme (Fig.…”
Section: Phospholyasesmentioning
confidence: 99%
See 1 more Smart Citation